2021
DOI: 10.1186/s12920-021-01123-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms with insulin secretion, insulin sensitivity, and diabetes in women with a history of gestational diabetes mellitus

Abstract: Background This study investigated whether single nucleotide polymorphisms (SNPs) reported by previous genome-wide association studies (GWAS) to be associated with impaired insulin secretion, insulin resistance, and/or type 2 diabetes are associated with disposition index, the homeostasis model assessment of insulin resistance (HOMA-IR), and/or development of diabetes following a pregnancy complicated by gestational diabetes mellitus (GDM). Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…The first of these is rs3934729 located near ADCY5 , a gene shared by T2DM adj BMI, FG adj BMI and PCOS and overlapping a suggestively significant T2DM adj BMI–PCOS local genetic correlation region chr3:11019665-13070799. Variation in ADCY5 increases fasting glucose levels and type 2 diabetes risk through altered expression in beta cells and impaired glucose signalling [ 33 ] and has been found to decrease the disposition index (an indicator of insulin secretion capacity) in women with gestational diabetes after adjusting for BMI [ 34 ]. Variation in ADCY5 has also been shown to affect ovarian morphological-related traits in bovines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first of these is rs3934729 located near ADCY5 , a gene shared by T2DM adj BMI, FG adj BMI and PCOS and overlapping a suggestively significant T2DM adj BMI–PCOS local genetic correlation region chr3:11019665-13070799. Variation in ADCY5 increases fasting glucose levels and type 2 diabetes risk through altered expression in beta cells and impaired glucose signalling [ 33 ] and has been found to decrease the disposition index (an indicator of insulin secretion capacity) in women with gestational diabetes after adjusting for BMI [ 34 ]. Variation in ADCY5 has also been shown to affect ovarian morphological-related traits in bovines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that gene variants may be associated with disease susceptibility by gene-gene interaction or affecting complex traits, such as mRNA/protein/methylation levels, biochemical indicators, etc. (14,15). Liu C et al found that ACE2 variants can significantly affect blood pressure (SBP or DBP) and blood lipid (TG, TC, HDL-C, or LDL-C) and regulate the onset of T2DM and its complications (33).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that gene variants may be associated with disease susceptibility by gene–gene interaction or affecting complex traits, such as mRNA/protein/methylation levels, biochemical indicators, etc. ( 14 , 15 ). Liu C et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prasad et al have shown that the IRS1 rs2943641 C allele is associated with increased insulin resistance (HOMA-IR). Their study demonstrated the genetic susceptibility of women with a history of GDM to impaired insulin secretion and sensitivity, and consequently to the development of diabetes [ 32 ]. In our study, the IRS1 TT genotype was associated with higher fasting glucose levels in women with GDM.…”
Section: Discussionmentioning
confidence: 99%